2016
DOI: 10.1137/15m1009603
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Local Approximation Spaces for Component-Based Static Condensation Procedures

Abstract: Abstract. In this paper we introduce local approximation spaces for component-based static condensation (sc) procedures that are optimal in the sense of Kolmogorov. To facilitate simulations for large structures such as aircraft or ships, it is crucial to decrease the number of degrees of freedom on the interfaces, or "ports," in order to reduce the size of the statically condensed system. To derive optimal port spaces we consider a (compact) transfer operator that acts on the space of harmonic extensions on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
111
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(115 citation statements)
references
References 40 publications
1
111
0
Order By: Relevance
“…Recently, port spaces that are optimal in the sense of Kolmogorov and thus minimize the approximation error among all port spaces of the same dimension have been introduced in [24]. The approach in [24] generalizes the idea of separation of variables by connecting two components at the port for which we wish to construct the port space and consider the space of all local solutions of the partial differential equation (PDE) with arbitrary Dirichlet boundary conditions on the ports that lie on the boundary of the two-component system. From separation of variables we anticipate an exponential decay (of the higher modes) of the Dirichlet boundary conditions to the interior of the system.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, port spaces that are optimal in the sense of Kolmogorov and thus minimize the approximation error among all port spaces of the same dimension have been introduced in [24]. The approach in [24] generalizes the idea of separation of variables by connecting two components at the port for which we wish to construct the port space and consider the space of all local solutions of the partial differential equation (PDE) with arbitrary Dirichlet boundary conditions on the ports that lie on the boundary of the two-component system. From separation of variables we anticipate an exponential decay (of the higher modes) of the Dirichlet boundary conditions to the interior of the system.…”
Section: Introductionmentioning
confidence: 99%
“…In [6] it has been shown that by employing methods from randomized numerical linear algebra an extremely accurate approximation of those optimal port spaces can be computed in close to optimal computational complexity. To account for variations in a material or geometric parameter in [24] a parameter-independent port space is generated from the optimal parameter-dependent port spaces via a spectral greedy algorithm. It is further numerically demonstrated in [24] that the optimal port spaces often outperform other approaches such as Legendre polynomials [13] or empirical modes [7]; also an exponential convergence can be observed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations